2023
DOI: 10.1021/acs.jpca.2c06623
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Based Mechanism for Fluoromethane Combustion I: Thermochemistry and Abstraction Reactions

Abstract: A new detailed chemical kinetic mechanism is presented for small fluorinated hydrocarbons. Ab initio electronic structure theory is used to provide heats of formation with subchemical accuracy. The ANL0 method is extended to include fluorine. The resulting heats of formation at 0 K are in excellent agreement with 36 benchmark species in the Active Thermochemical Tables, with a mean error of μ = −0.02 kJ/mol and a standard deviation of σ = 0.91 kJ/mol. The thermophysical properties for 92 small-molecule H/C/O/F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…The energies for the C 2 PFCA are obtained from Goldsmith and co-workers, and the Third Millennium Database values are used for the C 1 and C 2 saturated alkanes. Thus, looking more closely at C 3 and C 4 values, the deviation in the enthalpies is minimal, whereas the deviations across the board for the entropies of the C 1 –C 4 compounds remain largely the same whether considering the best values (either the Third Millennium Database, this work’s calculations, or a combination of calculations using a 0 K energy sourced from either ATcT or Goldsmith and co-workers). This suggests that there is a difference between the more expensive methods used for treating C 1 –C 4 compounds and the DFT-level values for C 5 –C 8 compounds, and in future works, a correction factor could be applied to the DFT-level calculations in order to obtain more accurate 0 K enthalpies of formation while balancing computational cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energies for the C 2 PFCA are obtained from Goldsmith and co-workers, and the Third Millennium Database values are used for the C 1 and C 2 saturated alkanes. Thus, looking more closely at C 3 and C 4 values, the deviation in the enthalpies is minimal, whereas the deviations across the board for the entropies of the C 1 –C 4 compounds remain largely the same whether considering the best values (either the Third Millennium Database, this work’s calculations, or a combination of calculations using a 0 K energy sourced from either ATcT or Goldsmith and co-workers). This suggests that there is a difference between the more expensive methods used for treating C 1 –C 4 compounds and the DFT-level values for C 5 –C 8 compounds, and in future works, a correction factor could be applied to the DFT-level calculations in order to obtain more accurate 0 K enthalpies of formation while balancing computational cost.…”
Section: Discussionmentioning
confidence: 99%
“…Enthalpies of formation at 0 K (including zero-point corrections) are calculated by adopting the isogyric reaction scheme for CHOF-containing compounds proposed by Goldsmith and co-workers in their high-level ANL0 study of abstraction reactions in fluoromethane combustion, as shown in eq . The reference species are CH 4 , H 2 O, CF 4 , and H 2 , for which the formation enthalpies are sourced from the Active Thermochemical Tables (ATcT), as shown in Table . .25ex2ex ( a 1 4 c ) normalC normalH 4 + b H 2 normalO + c 4 normalC normalF 4 + ( d 2 2 a b + c 2 ) H 2 H d C a O b F c …”
Section: Methodsmentioning
confidence: 99%
“…Yet another element is present in environmentally hazardous fluorine-containing H,C,O,F compound s whose thermochemistry and kinetics have been subjected to similar methods as detailed above. , Such “forever chemicals” represent an important class of persistent pollutants from uses such as flame retardants, surface coatings, food packaging, and refrigerant fluids that can be thermally destroyed by incineration. , To develop a mechanism for the thermal degradation of per- and polyfluorinated species, Sharma et al computed high level (ANL0) thermophysical properties for 92 small fluorinated species and used automated kinetics software to compute numerous rate coefficients for more than 70 H and F abstraction reactions . Paultre et al focused on pyrolysis strategies for the degradation and elimination of perfluoroalkyl carboxylic acids, an important subclass of forever chemicals, by mineralization.…”
Section: Fuels and Mechanismsmentioning
confidence: 99%
“…42,43 To develop a mechanism for the thermal degradation of per-and polyfluorinated species, Sharma et al computed high level (ANL0) thermophysical properties for 92 small fluorinated species and used automated kinetics software to compute numerous rate coefficients for more than 70 H and F abstraction reactions. 42 Paultre et al focused on pyrolysis strategies for the degradation and elimination of perfluoroalkyl carboxylic acids, an important subclass of forever chemicals, by mineralization. They used large scale computational studies to determine the favored degradation pathways for a number of species with 4−8 C atoms and a linear backbone.…”
Section: ■ Molecules and Reactionsmentioning
confidence: 99%
“…Computational modeling is often used to elucidate structure–reactivity relationships in PFASs through calculation of carbon–fluorine bond dissociation energies (BDEs), as nonfluorinated products observed in these reductive degradation experiments suggest that C–F bond cleavage is a key step in the mechanism. Due to their computational efficiency, density functional theory (DFT) and molecular mechanics (MM) methods are often employed to explain the structure activity relationships of different classes of PFASs. , The collection of these computed properties forms the basis for many machine learning applications. Notably, DFT-calculated BDEs of over 100 PFASs (564 distinct C–F BDEs) were used to predict C–F BDEs and identify structure–BDE relationships, and patterns in computed protein binding affinities were used to propose new PFASs for industrial use .…”
Section: Introductionmentioning
confidence: 99%